History of the Covid-19 Outbreak and Its Spread in Indonesia - Yunus, Nur Rohim (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
The Covid-19 pandemic has emerged as a worldwide public health emergency, impacting millions of individuals globally. Indonesia, being among the nations with the highest case count in Southeast Asia, is facing a substantial repercussion from this pandemic. The objective of this study is to examine the chronology of the Covid-19 epidemic in Indonesia, including its origins and subsequent transmission, while also identifying the obstacles encountered in mitigating its impact. This study employs a qualitative methodology, mostly relying on literature analysis. Information was acquired from several sources including scholarly journals, government reports, and pertinent news stories. According to the research findings, Covid-19 has rapidly disseminated across Indonesia since the initial case was identified in early March 2020. However, the obstacles to resolving these issues encompass a scarcity of healthcare resources, political and administrative instability, as well as deficiencies in infrastructure and accessibility. However, the government and many stakeholders' endeavors provide optimism that Indonesia can effectively combat this pandemic in the future.Keywords: Covid-19; History; Challenge; Mitigation Efforts